2015
DOI: 10.5604/12321966.1141379
|View full text |Cite
|
Sign up to set email alerts
|

The detection of areas in Poland with an increased prevalence of isolated cleft lip with or without cleft palate

Abstract: The study shows the usefulness of the LISA and Kulldorff's spatial analyses in epidemiological studies, including the etiology of congenital malformations. Because the two methods work in different ways, good results can be obtained when they are used together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
(49 reference statements)
1
4
1
1
Order By: Relevance
“…This is probably because our report includes only live‐born infants with nonsyndromic orofacial clefts, whereas the WHO WABD report included live and stillbirths, terminated pregnancies and neonatal deaths. Although several previous studies have shown an increase in the prevalence of orofacial clefts during the period studied, our data did not indicate an increase but showed only small fluctuations (ranging from 5.57 to 8.12 per 10 000) which were not statistically significant ( P = .92), indicating that the number of cases was relatively stable within the 13 years of study. This is similar to other reports of no overall change in prevalence of orofacial clefts over a 20‐ and a 50‐year period …”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This is probably because our report includes only live‐born infants with nonsyndromic orofacial clefts, whereas the WHO WABD report included live and stillbirths, terminated pregnancies and neonatal deaths. Although several previous studies have shown an increase in the prevalence of orofacial clefts during the period studied, our data did not indicate an increase but showed only small fluctuations (ranging from 5.57 to 8.12 per 10 000) which were not statistically significant ( P = .92), indicating that the number of cases was relatively stable within the 13 years of study. This is similar to other reports of no overall change in prevalence of orofacial clefts over a 20‐ and a 50‐year period …”
Section: Discussioncontrasting
confidence: 99%
“…A possible explanation for the increase might be due to improved surgical techniques and neonatal care resulting in reduced postnatal morbidity and mortality . As the aetiology of nonsyndromic orofacial clefts is partly genetic, survival of children born with orofacial clefts enables the transfer of genes responsible for the malformation to the next generations in accordance with Mendelian inheritance patterns and hence increases the number . The increased prevalence of orofacial clefts over the years may also be due to environmental factors such as maternal corticosteroids use, or smoking and alcohol consumption .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cleft lip is twice as common in boys as in girls, while cleft palate is twice more common in girls [2]. Comprehensive epidemiological studies of the prevalence of BCULP in children in various regions of Russia, Uzbekistan, Kazakhstan and Poland indicate an increase in the number of newborns with congenital malformations (CM) of the MFR (CMMFR) and predict a twofold growth of this pathology compared to the beginning of the 20th century [2][3][4][5][6]. This prediction is confirmed by the annual 1.38 times increase of the birth rate of children with CLCP for every 100 thousand of Стоматологической проблемой продолжает оставаться рождение детей с врождённой двухсторонней расщелиной верхней губы и нёба (ВДРВГН), которая требует поэтапного комплексного лечения.…”
mentioning
confidence: 99%
“…Расщелина верхней губы встречается в два раза чаще у мальчиков, чем у девочек, а расщелина нёба регистрируется в два раза чаще у девочек [2]. Комплексные эпидемиологические исследования распространённости детей с ВДРВГН в различных субъектах России, Узбекистане, Казахстане и Польше свидетельствуют о росте числа новорождённых с врождёнными аномалиями (ВА) челюстно-лицевой области (ЧЛО) и прогнозируют двукратное увеличение данной патологии по сравнению с началом XX века [2][3][4][5][6].…”
unclassified